2005
DOI: 10.1097/01.sla.0000171305.31703.84
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Refusal of Surgery Strongly Impairs Breast Cancer Survival

Abstract: Women who refuse surgery for breast cancer have a strongly impaired survival. This information might help patients who are hesitant toward surgery make a better informed decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 11 publications
5
61
0
2
Order By: Relevance
“…Although this was independent of stage (as recorded) and clinical variables such as jaundice and ascites, one cannot exclude other factors influencing the choice of treatment in determining outcome. We have no information on how many patients were offered, but refused (or did not comply with) conventional treatment-these are factors that are associated with a poor prognosis among cancer patients (Verkooijen et al, 2005;Hamidi et al, 2010). Regarding alternative medicine, patients classified as "unknown" for use of alternative medicine were more likely to die compared to those patients who had not used alternative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was independent of stage (as recorded) and clinical variables such as jaundice and ascites, one cannot exclude other factors influencing the choice of treatment in determining outcome. We have no information on how many patients were offered, but refused (or did not comply with) conventional treatment-these are factors that are associated with a poor prognosis among cancer patients (Verkooijen et al, 2005;Hamidi et al, 2010). Regarding alternative medicine, patients classified as "unknown" for use of alternative medicine were more likely to die compared to those patients who had not used alternative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 And in 1 study of women with newly diagnosed breast cancer, refusal of surgery occurred in under 2% of cases, and refusal was associated with decreased survival at 5 years. 8 To date, there have been no studies looking at the refusal of a range of medical and surgical interventions among patients with advanced chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, outcome data for patients who refuse surgical intervention are lacking. The only previous report, a review of the Geneva cancer registry during the period 1975-2000 [12], found that 1.3% of patients younger than 80 years with non-metastatic breast cancer declined surgery. Fifty percent of women refused without providing a clear reason, and 23% refused because of psychological problems such as depression.…”
Section: Discussionmentioning
confidence: 94%